1964
DOI: 10.1111/j.1476-5381.1964.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Adrenergic Blocking Action of Chlorpromazine

Abstract: Antagonism by chlorpromazine of the responses of the rabbit aortic strip and the rat seminal vesicle to adrenaline and noradrenaline fulfils the conditions of competitive antagonism. Chlorpromazine was a remarkably potent antagonist (pA2 approximately 14) of adrenaline and noradrenaline. In the cat anaesthetized with chloralose small doses (1.8 to 4.5 mg/kg) of chlorpromazine greatly reduced or reversed the pressor effect of adrenaline but the pressor effect of noradrenaline was unaffected. A larger dose (9 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1

Year Published

1965
1965
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…The increased pressor response in the rats treated with chlorpromazine-pentobarbital may be explained by the a-adrenergic blocking effect (Supek et al, 1962;Gokhale et al, 1964) and the potent inhibition of the central nervous system which occur in rats treated with these two agents in combination.…”
Section: Discussionmentioning
confidence: 99%
“…The increased pressor response in the rats treated with chlorpromazine-pentobarbital may be explained by the a-adrenergic blocking effect (Supek et al, 1962;Gokhale et al, 1964) and the potent inhibition of the central nervous system which occur in rats treated with these two agents in combination.…”
Section: Discussionmentioning
confidence: 99%
“…A similar suggestion had been made by other researchers regarding the uptake of labeled NE in peripheral tissues (22) and in the brain (1,23). However, as CPZ is an adrenergic blocking agent (16,17), the possibility remains that the enhancement of TB-induced NE depletion increases with hypersecretion of NE.…”
Section: Discussionmentioning
confidence: 83%
“…As CPZ has an adrenergic blocking effect (16,17), NE secretion was probably enhanced through a negative feedback control mechanism and the NE releasing action may have exceeded the suppression of NE decrease by its protection against the effect of RES on the granules. Yohimbine blocks presynaptic receptors, causing hypersecretion of NE (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This would explain why in the rabbit, in which adrenaline does not produce vasodilatation, chlorpromazine antagonizes adrenaline and noradrenaline pressor activities to the same extent. Also on this basis, if the p-receptor effects of adrenaline were blocked by an appropriate antagonist such as dichloroisoprenaline, then the differential antagonism would be lost also in the cat, and Gokhale et al (1964) have now shown this to be so.…”
Section: Discussionmentioning
confidence: 97%